2011
DOI: 10.1016/j.amepre.2011.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Coauthorship in Public Health Services and Systems Research

Abstract: Background Public health systems and services research (PHSSR) examines the organization, financing, and delivery of public health services and the impact of these activities on population health. An accurate description of this PHSSR is needed to empower funding agencies and other stakeholders, to coordinate PHSSR activities, and to foster the development of the field. Purpose To characterize the emerging community of researchers engaged in PHSSR. This study 1) describes dynamics of this growing community; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
1
10
0
1
Order By: Relevance
“…Previous research showed that economic factor will improve the research collaboration [47,48]. And as shown in Figure 6, similar to previous study in oncology or cardiovascular field, those economic powers such as USA, UK are in the center of the network, which play an vital role in the information dissemination and resources control in health management.…”
Section: Discussionsupporting
confidence: 66%
“…Previous research showed that economic factor will improve the research collaboration [47,48]. And as shown in Figure 6, similar to previous study in oncology or cardiovascular field, those economic powers such as USA, UK are in the center of the network, which play an vital role in the information dissemination and resources control in health management.…”
Section: Discussionsupporting
confidence: 66%
“…On the other hand, it is important to note some differences as well: although pathologies like Chagas disease, malaria and schistosomiasis have seen an increase in scientific research (COSTA LIMA et al The evolution in the number of co-authors who participate in the papers on this topic has seen exponential growth, a fact consistent with a more general trend of increased collaboration and especially coauthorship throughout the entire biomedical sector (VANZ & STUMPF 2010). However, the rise in collaboration also entails certain negative aspects, including unjustified hyperauthorship as well as other ethically In general, as in other topics, the most productive authors are those who demonstrate a high degree of collaboration (BALES et al 2008;BALES et al 2011). In this sense, it is important to note that although these researchers (identified as those who have published over 49 papers) have established collaborative links with a great number of authors, their stable and consolidated collaborators-that is, those with whom they regularly publish or have disseminated a considerable portion of their scientific output-are a relatively small in number.…”
Section: Discussionmentioning
confidence: 99%
“…This figure suggests that the most common way that research groups are organized depends on the existence of a principal author, who acts as its leader. According to network theory research, these authors are characterized by their collaborative ties with a large number of researchers [ 58 ], their status as highly productive authors [ 59 ], and the lowest geodesic distances registered in the network, which confers on them a leadership role due to their capacity to interact more directly and rapidly with other investigators [ 55 ]. Thus, these are researchers of reference, who are responsible for articulating the development of research in the area and facilitating wider collaborative relationships, the cohesion of scientific community, and the integration of new authors in the research groups.…”
Section: Discussionmentioning
confidence: 99%